2018
DOI: 10.1038/s41598-018-30687-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of fetal maceration grade on risk of maternal disseminated intravascular coagulation after intrauterine fetal death – A retrospective cohort study

Abstract: Disseminated intravascular coagulation (DIC) is a life-threatening event that is the endpoint of a pathologically activated cascade leading to excessive consumption of platelets culminating in bleeding. Several diseases are known to be associated with DIC, some of which may also occur during pregnancy or the puerperium. One of the potential risk factors that have been considered as a potential trigger for DIC is the retention of a highly macerated fetus after intrauterine fetal death (IUFD). However, sparse ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…In addition, the CI value of the AA group was low, which may be related to the patients receiving low‐dose aspirin or low‐molecular‐weight heparin in advance of undergoing TEG testing. Regarding stillbirths, Muin et al conducted a retrospective study on patients with in utero fetal death after a single birth and observed no significant difference in PC, PT, and other parameters, 25 which is consistent with our results. Unlike our non‐significant TEG results, Ikeuchi observed that patients with TA suffered abortion caused by decreased plasma plasminogen concentrations and increased C1 inactivator levels, and finally speculated that the decrease in urokinase inhibitory activity that leads to an increase in villous tissue fibrin activity is the potential reason for the miscarriage 26…”
Section: Discussionsupporting
confidence: 92%
“…In addition, the CI value of the AA group was low, which may be related to the patients receiving low‐dose aspirin or low‐molecular‐weight heparin in advance of undergoing TEG testing. Regarding stillbirths, Muin et al conducted a retrospective study on patients with in utero fetal death after a single birth and observed no significant difference in PC, PT, and other parameters, 25 which is consistent with our results. Unlike our non‐significant TEG results, Ikeuchi observed that patients with TA suffered abortion caused by decreased plasma plasminogen concentrations and increased C1 inactivator levels, and finally speculated that the decrease in urokinase inhibitory activity that leads to an increase in villous tissue fibrin activity is the potential reason for the miscarriage 26…”
Section: Discussionsupporting
confidence: 92%
“…In case of stillbirth, PPH might be associated with retained placenta which was noted in a very high number of women (23%) in a retrospective chart review to evaluate stillbirth demographics, pregnancy and maternal risk factors, and complications of labour and birth [ 76 ]. Another attributable cause for this association was disseminated intravascular coagulation as reported by evidence [ 77 79 ] which definitely lead to massive blood loss. Though global data on causes of stillbirth is limited [ 80 ], evidence demonstrates that intrapartum complications, hypertension, diabetes, infection, placental impairment, and pregnancy lasting longer than forty weeks are potential causes of stillbirth [ 81 ]; and these causes have been identified to be risk factors for PPH [ 22 , 82 ].…”
Section: Discussionmentioning
confidence: 84%
“…This timing is not possible to determine, unless induced through termination of pregnancy. During the maceration process, enzymatic autolysis of cells and tissues leads to fetal epidermal desquamation, skin reddening, and oedema of the internal organs . The severity and extent of these changes are graded by pathologists at external assessment of the body and believed to correlate with the length of the intrauterine retention of the fetus .…”
Section: Discussionmentioning
confidence: 99%
“…During the maceration process, enzymatic autolysis of cells and tissues leads to fetal epidermal desquamation, skin reddening, and oedema of the internal organs . The severity and extent of these changes are graded by pathologists at external assessment of the body and believed to correlate with the length of the intrauterine retention of the fetus . This rapid degradation process, occurring at maternal body temperature, is in contrast to the presumed slower tissue breakdown after fetal delivery prior to autopsy (ie, the postmortem interval), where the body is typically preserved in a refrigerated environment.…”
Section: Discussionmentioning
confidence: 99%